Benefit distribution and stability analysis of enterprises' technological innovation cooperation alliance. (November 2021) - Jiang, Xinghua; Wang, Lingfang; Cao, Bin; Fan, Xinyu
Highlights: A fair benefit distribution mechanism based on Shapley value is proposed. A positive synergetic effect makes enterprises join technological cooperation innovation alliance. The proposed benefit distribution mechanism belongs to a core of our cooperative game. Our model can help enterprises take targeted resource investment decisions. Abstract: Aiming at the stability problem of the technological innovation cooperation alliance formed by multiple enterprises, the cooperative game theory is used to analyze the benefit distribution mechanism of technological innovation cooperation among enterprises. Based on the amount of resources invested by enterprises in technological innovation cooperation alliances, a profit model for enterprise technological innovation cooperation is constructed. According to the Shapley value method, a profit distribution mechanism that can maintain a stable cooperative relationship is proposed, which is explicitly explained by application examples. We find that when the synergic coefficient of cooperation between enterprises is not less than 0, each enterprise can increase the benefits of technological innovation through cooperative alliances. The benefit distribution mechanism of the Shapley value method can maintain the stability of enterprise technological innovation cooperation alliance. The enterprises who participate in the alliance can make targeted resource investment decisions based on different parameters through our analytical analysis. Our results show that these parameters, namely the contribution coefficient and degree of the synergetic effect have positive affect on the benefits to the enterprises in the alliance, while the cost coefficient of invested resources has negative affect on the benefits to the enterprises in the alliance.